Model manajemen sekolah berbasis modal sosial untuk meningkatkan kinerja sekolah di era global - Wartomo Wartomo (At Turots: Jurnal Pendidikan Islam, 2022)
This study aims to produce a product in the form of a school management model that is used to improve school performance in SD (Elementary School) Patuk District, Gunungkidul Regency, through a research approach, with the Research and Development (R&D) model of the Dick and Carey development design. The final product of this research is a social capital-based school management model that has been evaluated by education management experts and education management practitioners as well as a limited test. Based on the results of research on the social capital-based school management model to improve school performance in the global era in elementary schools in Patuk District, Gunungkidul Regency, as indicated by the ability of school principals to motivate teachers and students, complete facilities and infrastructure, learning media, supporting books, creating a comfortable, healthy and conducive school organizational climate, so as to create a sense of comfort for students, and he must have dimensions of personality, managerial, entrepreneurial, supervision, and social competencies, while teachers always improve their professionalism, as well as parents or guardians of students cooperate with the school well, then this is supported by the government with the help of educational equipment. So, the social capital-based school management model is statistically proven to be effective in improving school performance in the global era.